醫生和家庭共決模式與多元主義: Shared Physician- and Family-based Decision Making, and Pluralism - CHAN, Ho Mun (International Journal of Chinese & Comparative Philosophy of Medicine, 2013)
LANGUAGE NOTE | Document text in Chinese; abstract in English only. For historical reasons, medical practice in Hong Kong is regulated by a legal system inherited from the UK. The system is in the liberal tradition. Po alleged that the Health Authority’s “Guidelines on Life-sustaining Treatment in the Terminally Ill” illustrate the practice of the family co-determination model in Hong Kong. This paper argues that on the contrary, due to the legal constraints with which the guidelines must comply, they carry a very strong liberal flavor. There are limitations to documentary research. To understand the practice in Hong Kong, we need to conduct empirical studies on the views of healthcare professionals, patients, and their families, and how they make decisions in real-life situations. Due to the cultural influence from both the East and the West, some degree of pluralism survives in Hong Kong. My empirical study shows that the shared physician- and family-based decision making model is most popular in Hong Kong, while a significant minority opts for the liberal model. DOWNLOAD HISTORY | This article has been downloaded 59 times in Digital Commons before migrating into this platform.